Necessary elements of precautionary management: implications for the Antarctic toothfish. Issue 4 (14th May 2016) - Abrams, Peter A; Ainley, David G; Blight, Louise K; Dayton, Paul K; Eastman, Joseph T; Jacquet, Jennifer L
Abstract: We review the precautionary approach to fisheries management, propose a framework that will allow a systematic assessment of insufficient precaution and provide an illustration using an Antarctic fishery. For a single‐species fishery, our framework includes five attributes: (1) limit reference points that recognize gaps in our understanding of the dynamics of the species; (2) accurate measures of population size; (3) ability to detect population changes quickly enough to arrest unwanted declines; (4) adequate understanding of ecosystem dynamics to avoid adverse indirect effects; and (5) assessment of the first four elements by a sufficiently impartial group of scientists. We argue that one or more of these elements frequently fail to be present in the management of many fisheries. Structural uncertainties, which characterize almost all fisheries models, call for higher limit points than those commonly used. A detailed look into the five elements and associated uncertainties is presented for the fishery on the Antarctic toothfish in the Ross Sea (FAO/CCAMLR Area 88.1, 88.2), for which management was recently described as 'highly precautionary'. In spite of having features that make the Ross Sea fishery ideal for the application of the precautionary approach, gaps in our knowledge and failure to acknowledge these gaps mean that current regulation falls short of being sufficiently precautionary. We propose some possible remedies.